2016
DOI: 10.1016/j.jns.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic pachymeningitis

Abstract: Hypertrophic Pachymeningitis (HP) denotes inflammation and thickening of the dura mater that can be idiopathic or secondary to a wide variety of conditions. Clinically, HP can present as debilitating headaches and cranial nerve defects but in other cases may be completely asymptomatic. We aimed to determine the relative incidence of different etiologies of HP and compare their associated imaging findings. Additionally, we sought to compare the clinical features of the underlying syndromes. We retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 32 publications
6
39
1
6
Order By: Relevance
“…There have been reported significant overlaps in the distribution pattern of dural enhancement among patients with MPO–ANCA positive HP, PR3-ANCA positive HP, immune-mediated, and idiopathic HP, and there is no consensus on the correlation between dural enhancement pattern and HP etiology [27, 39]. But fortunately, recent imaging studies indicated that most patients with MPO–ANCA positive HP have the CNS-limited form and less frequent leptomeningeal or parenchymal involvement than those with PR3-ANCA-positivity [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…There have been reported significant overlaps in the distribution pattern of dural enhancement among patients with MPO–ANCA positive HP, PR3-ANCA positive HP, immune-mediated, and idiopathic HP, and there is no consensus on the correlation between dural enhancement pattern and HP etiology [27, 39]. But fortunately, recent imaging studies indicated that most patients with MPO–ANCA positive HP have the CNS-limited form and less frequent leptomeningeal or parenchymal involvement than those with PR3-ANCA-positivity [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…We collected clinical, laboratory, imaging, and therapeutic data from these patients from our electronic medical records system. MRI enhancements were categorized by their locations, distributions, and patterns according to a definition described by Hahn et al [6]. Locations were identified by an experienced radiologist.…”
Section: Methodsmentioning
confidence: 99%
“…Pachymeningitis secondary to IgG4-RD is a form of hypertrophic pachymeningitis characterised by localised or diffuse inflammation and thickening of the meninges (mostly dura mater)—cerebral, spinal or rarely both [15, 5355]. Infectious, inflammatory and neoplastic causes need to be considered.…”
Section: Neurological Manifestations Of Igg4-rdmentioning
confidence: 99%
“…Infectious, inflammatory and neoplastic causes need to be considered. Of the inflammatory causes, sarcoidosis, granulomatosis with polyangiitis (GPA), rheumatoid arthritis (RA), Sjögren’s syndrome and IgG4-RD are the most common [15, 54, 55]. The prevalence of hypertrophic pachymeningitis has been evaluated in a Japanese national survey and reported to be 0.949 cases per 100,000, with pachymeningitis due to IgG4-RD being observed in 8.8%, second only to anti-neutrophil cytoplasmic antibody (ANCA)-related pachymeningitis [56].…”
Section: Neurological Manifestations Of Igg4-rdmentioning
confidence: 99%
See 1 more Smart Citation